Contribution of health to economic development: A survey and overview - Muhammad Jami Husain (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
The policies for better health, poverty reduction, and less inequality, throughout the world, require thorough understanding of both the processes and causal paths that underlie the intricate relationship between health and wealth (income). This is deemed difficult, contingent, and only partially understood. The adage 'health is wealth' is still, primarily, an intuitive proposition. A vast majority of researchers instead present theoretical and empirical arguments of the reverse proposition, i.e. 'wealth is health'. A recent strand of the literature, however, reflects changes in the perceptions: improvements of health and longevity are no longer viewed as a mere end- or by-product of economic development; but argued as one of the key determinants of, and therefore means to achieve, economic development and poverty reduction. Hence, better health does not have to wait for an improved economy; rather, measures to reduce the burden of disease, to give children healthy childhoods, to increase life expectancy etc. will in themselves contribute to creating richer economies. Drawing on the traditional and emerging perspectives on the health-income relationship, this literature review presents a non-exhaustive survey of existing methodological approaches and their results that are applied to track and measure how health influences economic outcomes.
Keywords: I10; O40; J11; 330; Health; income; economic growth; life expectancy; mortality; causality; Gesundheitspolitik; Armutspolitik; Einkommen; Entwicklung; Lebensstandard; Entwicklungsländer